2017
DOI: 10.24820/ark.5550190.p010.302
|View full text |Cite
|
Sign up to set email alerts
|

Generation and reactions of thiirenium ions by the Cation Pool method

Abstract: Thiirenium ions generated and accumulated by low-temperature electrochemical oxidation of disulfides in the presence of alkynes were successfully observed by low-temperature NMR, Raman, and mass spectroscopies and were found to be stable at temperatures below −40 °C. The thiirenium ions showed ambident reactivity toward subsequently added nucleophiles to give either disubstituted alkenes or alkynes depending on the nature of the nucleophiles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…In these cases, the RS + or RSe + part is cleaved off, and an alkene or alkyne is formed. In sterically unprotected thiiranium and seleniranium ions, the attack by nucleophiles happens mostly at the C atom of the three‐membered rings, [6b, 8–14] very similar to the thiirenium ions [2d] . This is also the case during the fluorothiolation and fluoroselenation of alkenes and the fluoroselenation of alkynes [36, 37, 7] .…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…In these cases, the RS + or RSe + part is cleaved off, and an alkene or alkyne is formed. In sterically unprotected thiiranium and seleniranium ions, the attack by nucleophiles happens mostly at the C atom of the three‐membered rings, [6b, 8–14] very similar to the thiirenium ions [2d] . This is also the case during the fluorothiolation and fluoroselenation of alkenes and the fluoroselenation of alkynes [36, 37, 7] .…”
Section: Resultsmentioning
confidence: 95%
“…This is also the case during the fluorothiolation and fluoroselenation of alkenes and the fluoroselenation of alkynes [36, 37, 7] . But there are examples known where the RS + group is transferred from thiirenium ions to transition metal complexes or C nucleophiles [38, 2d] . Finally, we want to point to the transition of RS + and RSe + groups in thiiranium, seleniranium, or thiirenium ions to alkenes and alkynes, where the C−C‐multiple bond preferably interacts with the heteroatom of the three‐membered ring [1g, 6, 2d, 39] …”
Section: Resultsmentioning
confidence: 99%
“…To date, the most commonly used methods for calculating organic molecules are the density functional theory methods, in particular, the B3LYP functional. 21,22 The B3LYP functional with 6-31G* basis set has been successfully used for the study of thiirenium cations and acetylene sulfides, 23 as well as for thiiranium cations. 24 The double-hybrid functionals that have appeared relatively recently show good agreement with precision calculations, but they require more significant computing resources compared to hybrid ones.…”
Section: Computational Detailsmentioning
confidence: 99%
“…42 It has been found that by anodic oxidation, symmetrical alkynes can undergo difunctionalization via thiirenium ion intermediates (Scheme 1b). 43 In the present year, Kesharwani and co-workers reported the application of DMTSF to promote the electrophilic activation and internal cyclization of alkynyl thioanisoles. 44 In the continuation of our program 45−48 considered exploring its reaction with alkynes, which would offer a direct activation and addition strategy for the sulfenotriflation of alkynes with a readily available and easyto-handle thiolating reagent (Scheme 1c).…”
mentioning
confidence: 99%
“…Therefore, achievements in this field require either an acid activator , or much more active sulfonium salts, which were generally formed in situ by the treatment of sulfoxides with trifluoromethanesulfonic anhydride (Scheme a). An early study preliminarily found that vinyl triflate products could be obtained by the reaction of alkynes with dimethyl sulfide ditriflate (prepared by the treatment of dimethyl sulfoxide with Tf 2 O), though with limited chemo- and stereoselectivity . It has been found that by anodic oxidation, symmetrical alkynes can undergo difunctionalization via thiirenium ion intermediates (Scheme b) . In the present year, Kesharwani and co-workers reported the application of DMTSF to promote the electrophilic activation and internal cyclization of alkynyl thioanisoles .…”
mentioning
confidence: 99%